2020
DOI: 10.1002/admt.202000090
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Devices Using Nanoparticle Chains as Universal Building Blocks with Simple Filtration‐Based Fabrication and Quantum Sensing

Abstract: Self‐assembled micrometer long gold nanoparticle chains are used as building block to fabricate a range of flexible devices to monitor human physiological signals by an easy filtration method. The chains serve as the base material for all the devices and their interconnects and contact pads as well. The micrometer long chains are an array of nanoparticles with gaps of 1–2 nm between adjacent particles. The gaps serve as quantum tunneling barrier and their modulation is basis of signal sensing in these devices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Centrifugation was used to deposit 1D nanoparticle chains . The Ca 2+ ions in the bridge were precipitated to form Ca­(OH) 2 that cements adjacent particles, similar to other ion systems, , including Ca 2+ . , The N 3 morphology, with individual 1D chains, is clearly visible in SEM images (Figure a, inset (a1)). The number of percolation paths between the electrodes depends on the array width, so a well-defined pattern was critical to obtain consistent results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrifugation was used to deposit 1D nanoparticle chains . The Ca 2+ ions in the bridge were precipitated to form Ca­(OH) 2 that cements adjacent particles, similar to other ion systems, , including Ca 2+ . , The N 3 morphology, with individual 1D chains, is clearly visible in SEM images (Figure a, inset (a1)). The number of percolation paths between the electrodes depends on the array width, so a well-defined pattern was critical to obtain consistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, studies in the last decade have shown that a special architecture of 2D nanoparticle necklace network (N 3 ) arrays of one-dimensional (1D) chains of 10 nm Au particles exhibits an identical I – V characteristic with a robust V T as high as 5.5 V at room temperature and a ζ larger than 3. Similar to conventional nanoparticle arrays, the V T increases linearly as the temperature decreases from RT to 4 K . Here, we explore this anomalous, unexpected behavior of N 3 architectures in open-gate field effect transistor (ogFET) configuration at RT.…”
Section: Introductionmentioning
confidence: 93%
“…The effects of conductive filler types, including NWs, nanoparticles, nanolayers, and aerogels, have been studied . Moreover, several common processes, including mixing methods (such as melt-mixing and solution-mixing), , coating techniques (containing transferring, spraying, and filtration methods), and chemical synthesis, have been systematically reported in many studies, demonstrating their various advantages and disadvantages . For the hybrid microstructure, many efforts have been focused on the simulation and fabrication of stretchable structures, including wavy geometries, percolating networks, helical structures, serpentines, and mesh shapes to generate microcracks and wrinkles to improve the sensing range and sensitivity. , Some studies reported hybrid stretchable sensors utilizing different fillers, such as CNT and Ag-NW, to combine each advantage to obtain better-performing sensors. , Moreover, some reports focused on the buckling and slippage phenomenon when stretching for microstructure. , However, the sensing effect disparity between different fillers with the same dimension has not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…To address the equally important issue of fabrication of low-cost electrodes that can survive extreme bending, twisting, and stretching conditions, the current work demonstrates the utilization of room-temperature solution-processed platinum–gold (Pt–Au) nanoparticle chains . The mesh of metallic Pt–Au nanochains has high conductivity and offers resistance against oxidation over the conventionally used Ag and Cu nanowire electrodes in flexible devices. Further, the nanochain electrodes are deposited by a simple vacuum filtration-based method, a cost-effective alternative to sputtering and thermally evaporated metal electrodes. , The stretchable photodetector assembly of a 1 wt % PS-MAPbI 3 film with the underlying Pt–Au nanochain electrodes exhibits ultralow dark currents in the range of ∼10 –11 A, a high light switching ratio on the order of ∼10 3 , and can sustain a high lateral strain up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…36−39 Further, the nanochain electrodes are deposited by a simple vacuum filtration-based method, a costeffective alternative to sputtering and thermally evaporated metal electrodes. 40,41 The stretchable photodetector assembly of a 1 wt % PS-MAPbI 3 film with the underlying Pt−Au nanochain electrodes exhibits ultralow dark currents in the range of ∼10 −11 A, a high light switching ratio on the order of ∼10 3 , and can sustain a high lateral strain up to 100%.…”
Section: Introductionmentioning
confidence: 99%